Usefulness of patient-reported outcomes to assess the effectiveness of topical hormonal therapy for gynecologic symptoms after antihormonal treatment for breast cancer. Issue 3 (2nd July 2020) - Jain, Amit L.; Jamy, Omer; Mullins, Janice; Usman, Rana Muhammad; Hare, Felicia; Valasareddy, Poojitha; Chaudhry, Amina; Ryder, Julie; Smith, Justin R.; Miller, Emily; Ranganath, Harsha; Schwartzberg, Lee; et al.
Abstract: The aim of this retrospective study was to assess the efficacy of topical hormonal therapy (THT) to relieve vaginal symptoms resulting from antihormonal therapy in women with hormone receptor–positive breast cancer. A total of 74 breast cancer patients who received THT for vaginal complaints were retrospectively identified and statistically matched with 74 control breast cancer patients with vaginal complaints with no documented use of THT. Symptom scores were recorded from the center's proprietary patient-reported outcomes database, Patient Care Monitor (ConcertoHealthAI, Boston). A baseline score was noted at the initiation of antihormonal therapy and was followed at 6 and 12 months. The median differences between baseline, 6-month, and 12-month scores were analyzed. Repeated measures analysis of variance assessed the impact of topical hormonal replacement. There was no statistically significant difference in score change between the two groups at 6 and 12 months. In the active THT group, there were no statistically significant differences in vaginal complaints or sexual problems over time: F (2, 146) = 0.99, P = 0.369; and F (2, 146) = 1.56, P = 0.217 , respectively. In this study, the use of topical hormonal replacement was not effective in alleviating vaginal symptoms.